The Parody of Musical Instruments in Medieval Iconography - Sandra Pietrini (Revista de Poética Medieval, 2018)
The vast field of musical iconography during the Middle Ages must necessarily deal with the rich and surprising imagery of western manuscripts, showing a fanciful proliferation of playing creatures and bizarre deformations, sometimes inspired by exotic suggestions. In marginal miniatures of 14th century we can discover an interesting and puzzling topic: the parody of entertainers, with hybrid men playing a vielle with tongs, mermaids or apes playing jawbones and so on. The spreading of this topic in medieval iconography is linked to a satirical purpose aimed at professional entertainers, harshly condemned by Christian writers. Strange instruments made out of everyday objects like grills and distaffs, or ‘exotic’ animals like peacocks, mingle in the grotesque underworld of marginal miniatures, in which the noble art of music is often replaced by the cacophonous noises suggested by the devil.